The Mojave-Sonora Megashear Hypothesis: Development, Assessment, and Alternatives 2005
DOI: 10.1130/0-8137-2393-0.671
|View full text |Cite
|
Sign up to set email alerts
|

Isotope provinces in Laramide and mid-Tertiary igneous rocks of northwestern Mexico (Chihuahua and Sonora) and their relation to basement configuration

Abstract: We have identifi ed fi ve distinct isotope provinces in northwestern Mexico in a study of the Sr, Nd, and Pb isotope geochemistry of Laramide and mid-Tertiary igneous rocks in Sonora and Chihuahua as well as adjacent portions of southwestern United States. Province A, in northern Sonora, is characterized by very unradiogenicNd and Pb isotopic compositions and radiogenic Sr isotopic compositions. Unradiogenic Nd and radiogenic Sr and Pb isotopic compositions characterize Province B, in central Sonora. Provinces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…The sample shows very low CaO (0.11%) and high K 2 O (6.4%) with relatively high loss on ignition (LOI-2.6%). The value of initial 87 Sr/ 86 Sr in sample 7 as well as of sample 3 are somewhat higher compared to other samples reported from the area (Damon et al, 1983;Housh and McDowell, 2005; see also Table 2), differences could be caused by hydrothermal alteration as it has been observed in oceanic basalts and in the volcanic geothermal field of Los Azufres (Verma, 1992;Verma et al, 2005). The isotopic values of Sr and Nd from La Caridad and Cananea are very similar suggesting the same origin for the magmas in both districts.…”
Section: La Caridad Districtmentioning
confidence: 57%
See 2 more Smart Citations
“…The sample shows very low CaO (0.11%) and high K 2 O (6.4%) with relatively high loss on ignition (LOI-2.6%). The value of initial 87 Sr/ 86 Sr in sample 7 as well as of sample 3 are somewhat higher compared to other samples reported from the area (Damon et al, 1983;Housh and McDowell, 2005; see also Table 2), differences could be caused by hydrothermal alteration as it has been observed in oceanic basalts and in the volcanic geothermal field of Los Azufres (Verma, 1992;Verma et al, 2005). The isotopic values of Sr and Nd from La Caridad and Cananea are very similar suggesting the same origin for the magmas in both districts.…”
Section: La Caridad Districtmentioning
confidence: 57%
“…To the north of the limit of the Sonora Allochthonous (Poole et al, 2005) (Mcdowell et al, 1999). This, allow us to speculate on the absence of Sonoran proterozoic basement in this zone and relate the isotopic data to a pre-Laramidic geologic history similar to that of central Chihuahua (Housh and Mcdowell, 2005).…”
Section: La Caridad Districtmentioning
confidence: 99%
See 1 more Smart Citation
“…Outcrops of these rocks are widespread in Sonora, and recent contributions have improved the knowledge of their regional stratigraphy, geochronology, geochemical and radiogenic isotopic composition, to better constrain the timing, nature and implication of basement variations, associated mineralization, and petrogenesis (Roldán-Quintana, 1991, McDowell et al, 2001, Valencia-Moreno et al, 2001, Valencia-Moreno et al, 2003, Iriondo et al, 2004, Housh and McDowell, 2005, Nourse et al, 2005, Noguez-Alcántara et al, 2007, Roldán-Quintana et al, 2009, Pérez-Segura et al, 2009, González-León et al, 2011, Pérez-Segura et al, 2013, Del Río Salas et al, 2013.…”
Section: Introductionmentioning
confidence: 99%
“…U-Pb zircon ages were obtained by laser ablation inductivelycoupled plasma mass spectrometry (LA-ICPMS) in the Centro de Geociencias, UNAM following procedures described in Solari et al (2010Solari et al ( , 2015 [results are reported in Supplemental Table A], and by laser ablation-multicollector-inductively coupled plasma-mass spectrometry (LA-MC-ICP-MS) at the Arizona LaserChron Center of the Department of Geosciences, University of Arizona, using the procedures described by Gehrels et al (2006) (Housh andMcDowell, 2005: González-León et al, 2011) Nd and Sr isotope values of Laramíde rocks in the Caborca block of central Sonora (Valencia-Moreno et al, 2001, Housh andMcDowell, 1995;González-León et al, 2011) Plutons of the study quadrangle (Wooden et al, 1988;Wooden and DeWitt, 1991) showing plots of the El Palofierral orthogneiss and the Laramide and syn-extensional plutons of the study area. Black stars are Pb isotope values reported from Paleoproterozoic granites of the Caborca terrane by Farmer et al (2005) and González-León et al (2011).…”
mentioning
confidence: 99%